The Development Of Contextual Teaching and Learning Based-Video on Reproductive System Concept for SMA - Erlianti, Susi; Widiyaningrum, Priyantini; Lisdiana, Lisdiana (Journal of Biology Education, 2017)
Learning video is proven to increase students learning experiences. The contextual approachrelates learning materials with the situation around the students and encourages them to apply theirknowledge. The reproductive system concept is closely related to the real life. This research would developa valid, feasible and effective learning video based on Contextual Teaching and Learning. The researchwas conducted in SMA Negeri 2 Rembang. Subjects in this research were 83 students. The resultsshowed validation scores by media experts and content experts are 83.33% and 91.67% with very validcriteria. The Results of teacher and student responses showed average scores of 93.75% and 86%respectively with very good criteria. The result of analysis on students cognitive learning of class XISCIENCES 1 and XI SCIENCES 3 gives average N-gain of 0.63 with moderate criteria. Assessment ofstudentsâ attitude of class XI SCIENCES 1 and XI SCIENCES 3 obtained an average score of 95,07%in very high criteria. It can be concluded that the learning video based on Contextual Teaching andLearning on the reproduction system concept developed has been valid, feasible and effectively applied tothe learning of grade XI SMA Negeri 2 Rembang.